PERBANDINGAN KUAT TEKAN MORTAR DENGAN MEMANFAATKAN COAL ASH WASTE - Yunanda, Mega (Jurnal Teknik Sipil, 2019)
The utilization of coal ash waste (Fly ash) which is processed into raw material in making mortar, is expected to be useful in daily life, in addition to improve the economy of the community, can also reduce the impact of environmental pollution due to waste from coal ash (Fly ash). And provide information to the public about the effect of addition of coal ash (Fly ash) to the quality of mortar. From the results of this study it can be seen that the strength of mortar pressure without the mixture of coal ash or normal is 109.33 kg / cm, while for the average compressive strength of mortar mixed with coal ash is 9%, 12%, and 15% respectively, were 156 kg / cm2, 125.33 kg / cm2, and 110.6 kg / cm2. From the results of the study. it can be seen that mortar strength is highest if the variation of coal ash mixture is 9% of cement amount. While mixing more than 9% of mortar compressive strength will decrease. Thus the use of coal ash with a content of 9% is the optimum mixture content in this mixture. If a mixture of coal ash exceeds that level, it will decrease the strength of mortar. This decrease is thought to be due to the less strong bonds between aggregates (mixed materials) on the use of coal ash over 9%